Piano Sonata no. 14 in C-sharp minor, op. 27, no. 2, edited by Bennett and Macfarren - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Bennett, William Sterndale, 1816-1875 (editor):::Contributor::::::::::::; Macfarren, Walter, 1826-1905 (editor):::Contributor:::::::::::: (London; United Kingdom; Edwin Ashdown, 2024)
Piano Sonata no. 14 in C-sharp minor, op. 27, no. 2, from "Sir William Sterndale Bennett's Edition of Beethoven's Sonatas for the Pianoforte," with revisions and fingerings by Walter Macfarren, published by Edwin Ashdown in London.